Strategi Penanganan Kelebihan Kapasitas Warga Binaan Pada Lembaga Pemasyarakatan Kelas IIA Salemba - Selly Filanda; Nida Handayani; Mawar Mawar; Muhammad Khairul Anwar (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Correctional Institution (Lapas) is a place to conduct training for prisoners and correctional students. The excess capacity at the prison is due to the high number of inmates entering the Class IIA Salemba Prison which is not directly proportional to the number of inmates who are free from criminal periods. The problem of excess capacity has an unfavorable impact on the inmates. This study aims to discuss the strategy for dealing with the excess capacity of inmates at the Class IIA Salemba Prison, using a qualitative approach and analyzed using Koteen's theory (1997). The results of the research on handling excess capacity in the Class IIA Salemba Prison by granting the rights of the inmates, trying to increase the capacity of the prison and using a family leadership pattern. The result is that the Class IIA Salemba Prison has a distinctive character and becomes a role model for other prisons in DKI Jakarta with obedience and punctuality in worship. The program strategy provides rehabilitation activities, fostering independence, personality and independent business. Resources become a strategy by providing service satisfaction, coaching and securing competent human resources, providing facilities, infrastructure and workload analysis to meet the needs of prisons. The institutional strategy develops a strategy that is implemented through changes to regulations for granting remissions with the abolition of Justice Collaborators, extension of Assimilation, progress of the Prisoners Development Assessment System (SPPN) and the addition of Class IIA Salemba Prison officers